Best growth condition for Gracilaria Manilaensis (rhodophyta) under different salinities, Ph and light intensities and its type of carrageenaan - Mohammad Noor, Normawaty; Mohamad Hidayat, Nor Salamah; Susanti, Deny; Mukai, Yukinori; Saad, Shahbudin (2017)
Seaweed from genus Gracilaria is well known for their characteristic as agarophyte and has the potential as source of carrageenan, a polysaccharides. For commercial production, an enormous amount of raw seaweed is required. Thus, mariculture can become the alternative way to meet the growing demand of seaweed as raw materials. Based on literatures, it is well documented that growth rate and carrageenan yield depend on environmental factors such as salinity, pH, temperature, light intensity and water movement. Therefore, in this study, growth rate and carrageenan yield of Gracilaria manilaensis, a red seaweed, were determined at different conditions. G. manilaensis was cultured under laboratory conditions in a 500 mL flask of seawater at different light intensities (100, 500 and 1000 lux), salinities (15, 20, 25 and 30 psu) and pH (7.6, 7.8, and 8.0) for 21 days. At the end of experiment, the growth rate was determined followed by carrageenan analysis. Then, the ground seaweed samples were used for Attenuated Total Reflection-Fourier Transform Infrared Spectroscopy (ATR-FTIR) to identify the carrageenan type of each treatment. From the analyses, the highest growth rate was observed at high light intensity, low salinity and slightly alkali pH (1000 lux, 15 psu and pH 7.6). Meanwhile, the carrageenan yield was highest at low light intensity, high salinity and more towards alkaline pH (500 lux, 25 psu and pH 8.0). This indicates that the quality of G. manilaensis in term of carrageenan content can be optimized under certain growth conditions. Analysis of carrageenan types showed that different types of carrageenan i.e. kappa, iota and lambda were observed under different conditions. Findings from this study provide important information in developing culture of Gracilaria for high biomass and/or for carrageenan production. The identification of different types of carrageenan from Gracilaria at different growth conditions indicates that this species has high potential to be commercialized however further study is needed to quantify carrageenan’s yield.